Regular Antenatal Care Visits Predict Good Knowledge Among Post-natal Mothers Regarding Entitlements of Health Programs in Western India - Mihir P. Rupani; Pathik M. Patel; Pooja R. Meena; Pooja P. Patel; Priskila A. Patel; Priya K. Paragda (Kerman University of Medical Sciences, 2019)
Janani-Shishu Suraksha Karyakram (JSSK) and Janani Suraksha Yojana (JSY) were launched with the objective of increasing institutional deliveries. But, its knowledge among the post-natal mothers is not known. This research evaluated the knowledge of two national health programs among post-natal mothers and found out the predictors of good knowledge about the entitlements of these programs. A cross-sectional study was conducted on a sample of consecutively recruited 339 post-natal mothers who had delivered in a tertiary care hospital of western India. Data were collected from November 2016 to February 2017 by interview method using a questionnaire with questions about knowledge regarding the entitlements of JSSK and JSY. Multivariable analysis was carried out for predictors of good knowledge. Among the 339 post-natal mothers, 30% had a good knowledge regarding JSSK. Only 24% had heard about JSSK; 54% knew regarding free transport to the place of delivery; only 22% and 13%, respectively knew about free inter-facility transport in case of complications for pregnant women and sick infants, while 96% knew regarding free drop-back facility. Only one-fourth of the mothers knew regarding monetary benefit under JSY, while 28% of them had actually received the benefit. The number of antenatal care visits, having an occupation and belonging to Hindu religion significantly predicts good knowledge among postnatal mothers regarding JSSK. Knowledge among the post-natal mothers regarding the entitlements of JSSK and JSY is less while comparing with published literature and needs improvement. Regular ante-natal care (ANC) visits might improve their knowledge of these programs. There is a need to create awareness among hospital staff for the provision of reimbursement of costs incurred by post-natal mothers. There is also a need to carry out demand generation activities among mothers regarding the entitlements of JSSK and JSY.